ANALISIS BEBAN KERJA KARYAWAN DALAM MENENTUKAN JUMLAH KEBUTUHAN KARYAWAN YANG IDEAL DI YAYASAN SOSIAL KAPILER INDONESIA - Azmi Mukhlis (2022)
Kapiler Indonesia is a social foundation in the form of an online platform that runs in the empowerment and mapping of orphanages in Indonesia. Kapiler Indonesia has a target to always develop and be able to compete with foundations engaged in the same field. To achieve this target, teamwork and a sufficient number of human resources are needed so that the work can be carried out properly. In this study, the main objective is to analyze the current workload of the mapping and empowerment division employees, and then the results of the workload analysis can be used as a basis for calculating the ideal number of employee needs. The method used in this study is a qualitative approach, then this study uses the Full Time Equivalent (FTE) calculation method to calculate the number of employee needs. After calculating with this method, it is known that the workload in the mapping and empowerment division is not balanced from 3 employees working, where 2 employees have normal workloads, and 1 employee with low workload or underload. Based on the calculation of the number of employees needed in the mapping and empowerment division is it 3 people or is it enough with the current number of employees. Keywords : Workload, Full Time Equivalent (FTE).